Neoliberal slavery and the immperial connection - Castellano Masías, Pedro (2014)
Neoliberal economy has been developed under promises of grater freedom and progress,paradoxically the capacity for human degradation within the logic of neoliberalcapitalism goes far beyond dominant criticism. It is not only that there is degradation ofwork life as a result of Taylorism and automation, not only greater ecological perils dueto the greenhouse effects of industrial performance, and it is not the case just thatinternational arrangements of the economic foster poverty and exclusion at theperiphery of capitalist neo-liberalism. We are experiencing now a radicalization ofhuman degradation in unexpected proportions to the point that slavery has come back tosupport economic growth and wealth accumulation, even though slavery is forbiddenalmost everywhere, reality is that in today’s world the economy is fed by slave work.In this paper we study the ways neo-liberalism has allowed for the development of anenslaving economical system. First at all we shall review the main evidences of what Icall the enslaving economy, second we shall move to discuss the Dynamics ofNeoliberal Slavery differentiating the Micro-Dynamics, Macro-Dynamics, and theMeso-Dynamics of Neoliberal Slavery. Finally it is presented proposals to face the fastgrowing development of slavery including interventions in organizations, education,political action, etc.